2016
DOI: 10.3201/eid2207.160116
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Chikungunya Virus and Frequency of Viremic Blood Donations during Epidemic, Puerto Rico, USA, 2014

Abstract: Deaths were rarely observed, but newborns and other vulnerable populations are at risk for severe complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 31 publications
2
84
0
Order By: Relevance
“…Patients with low-positive CHIKV viremia have been identified in other series, but the clinical presentation of and outcomes for such cases have not been evaluated [1720, 25]. In our study, 57.1% of CHIKV-positive patients had viremia that was below the quantifiable range in the ZCD assay.…”
Section: Discussionmentioning
confidence: 69%
“…Patients with low-positive CHIKV viremia have been identified in other series, but the clinical presentation of and outcomes for such cases have not been evaluated [1720, 25]. In our study, 57.1% of CHIKV-positive patients had viremia that was below the quantifiable range in the ZCD assay.…”
Section: Discussionmentioning
confidence: 69%
“…For example, if 25% of the population in Puerto Rico is already immune to Zika (27), coverage of 50% or 90% of women 9–49 would reduce prenatal infections in a subsequent outbreak to 5 or 2, respectively, per 1000 pregnancies (Figure 3B–C), compared with 192 in an unvaccinated, immunologically naive Puerto Rican population (Figure 3A). The expected impact under reduced vaccine coverage represented in this sensitivity analysis also approximates the impact under reduced vaccine efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Third, we determined the best fit parameter sets for the epidemiological variables using a least-squares approach. For Puerto Rico, we computed the human-to-mosquito transmission rate that produced a 23.5% attack rate, as observed during the Puerto Rico Chikungunya outbreak (27), and computed the mosquito seasonality parameters which best fit the observed Zika epidemic trajectory over the period January 17, 2016 through July 21, 2017 (28,29) (Figure S2). When not otherwise specified, we used the Puerto Rico best-fit attack rate as our base case.…”
Section: Methodsmentioning
confidence: 99%
“…Retrospective screening for chikungunya virus nucleic acid was performed on blood donations collected during June-December 2014, and the estimated detectable viremia was 0.65%, with a peak of 2.1% in October. Testing for chikungunya virus immunoglobulin M antibody of retained individual blood donation samples obtained during March 1-9, 2015, suggested that nearly 25% of the Puerto Rico population became infected during the previous year's epidemic (7). Because viremia is only present days after acute infection, immunoglobulin M antibody can provide a more precise estimate of the burden of recent infection.…”
Section: On June 17 2016 This Report Was Posted As An Mmwr Early Rementioning
confidence: 99%